ҚОСТАНАЙ ОБЛЫСЫНДАҒЫ СҮТ ЖӘНЕ СҮТ ӨНІМДЕРІНЕН ОҚШАУЛАНҒАН ПАТОГЕНДІ МИКРООРГАНИЗМДЕРДІҢ ТАРАЛУЫ ЖӘНЕ АНТИБИОТИКТЕРГЕ ТӨЗІМДІЛІГІ - K. Мәлікзада; Г. Алиева; M. Ерназарова; А. Габитова; Ж. Бермухаметов; П. Шевченко; Г. Чужебаева; Р. Рыщанова (Animal Health and Biosafety, 2026)
ABSTRACT: Antimicrobial resistance is one of the major global challenges in veterinary medicine and food safety. Contamination of raw milk and dairy products with antimicrobial-resistant opportunistic pathogenic microorganisms poses a significant risk to public health and necessitates continuous epidemiological and microbiological surveillance. The aim of this study was to determine the prevalence and antimicrobial resistance profiles of Staphylococcus aureus, Streptococcus agalactiae, and Escherichia coli isolates recovered from raw cow's milk and dairy products in the Kostanay Region. The study included raw milk samples collected from cows with clinical signs of mastitis and dairy products obtained from the retail market in the Kostanay Region Microorganisms were isolated using conventional bacteriological methods, and species identification was confirmed by Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS). Antimicrobial susceptibility was determined using the disk diffusion method, and the results were interpreted according to the European Committee on Antimicrobial Susceptibility Testing (EUCAST) guidelines. A total of 110 opportunistic pathogenic bacterial isolates were recovered, including 54 S. aureus, 34 E. coli, and 22 Str.agalactiae isolates. S. aureus isolates exhibited high resistance to β-lactam antibiotics, with resistance rates of 67% to ampicillin and 47% to benzylpenicillin. E. coli isolates demonstrated resistance primarily to fluoroquinolones, tetracyclines, and aminoglycosides, whereas all Str. agalactiae isolates were resistant to tetracycline. The findings indicate a widespread occurrence of antimicrobial-resistant opportunistic pathogenic microorganisms in raw milk and dairy products in the Kostanay Region. These results emphasize the importance of rational antimicrobial use in veterinary practice and the strengthening of microbiological surveillance. Furthermore, future studies should focus on the molecular genetic characterization of antimicrobial resistance and virulence genes in the recovered isolates. Such investigations will contribute to a better understanding of antimicrobial resistance dissemination and support the improvement of regional surveillance systems